A real-time data compression algorithm for gear fault signals. (June 2016) - Han, Shu; Liu, Xiaoming; Chen, Jia; Wu, Jin; Ruan, Xiaofei
Highlights: A real-time data compression algorithm based on ARMA model and SDT algorithm. ARMA-SDT is used for impact-type signals compression in gear fault detection systems. A formulation is developed to estimate compression threshold adaptively. An experiment platform and an engineering solution are designed. Experimental results confirmed the flexibility, stability and controllability. Abstract: A flexible, stable and controllable real-time algorithm of Auto-Regressive and Moving Average based on Swing Door Trending (ARMA-SDT) is proposed for the compression of impact-type signals in gear fault detection systems. The Auto-Regressive and Moving Average (ARMA) model is used to predict the variation trend of signal features. To guarantee the adaptability, an empirical equation is proposed to calculate the compression threshold of the Swing Door Trending (SDT). Based on the empirical equation and prediction results, dynamic self-regulation of compression threshold is realized, and the compression error always stays around a preconfigured value. Moreover, an experimental setup and an engineering solution are proposed to verify the usefulness, reliability, and stability of the proposed ARMA-SDT algorithm in data compression.